2020
DOI: 10.3892/ol.2020.12420
|View full text |Cite
|
Sign up to set email alerts
|

B3GNT3: A prognostic biomarker associated with immune cell infiltration in pancreatic adenocarcinoma

Abstract: Pancreatic cancer, one of the most malignant gastrointestinal tumors, is prone to liver metastasis. However, due to the lack of appropriate and comprehensive diagnostic methods, it is difficult to accurately predict the survival outcomes. Therefore, there is a need to identify effective biomarkers, such as UDP-GlcNAc: βGal β-1,3-N-acetylglucosaminyltransferase 3 ( B3GNT3 ), that predict the survival outcome of patients with pancreatic cancer. In the present study, based on data from 171 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…The levels of B3GNT3 protein were determined using the HPA database and western blot, indicating higher expression in LUAD tissues and LUAD cells than in normal lung tissues and human bronchial epithelial cells, respectively. Consistent with our findings, B3GNT3 was revealed as a carcinogenic factor by presenting higher expression in pancreatic cancer (16), early-stage cervical cancer (15), neuroblastoma (14), and endometrial cancer tissues than in normal tissues (29). In our study, high levels of B3GNT3 were associated with poor prognosis with advanced stage and higher mortality rates, which was also indicated in previous lung cancer (19) and non-small cell lung cancer studies (12).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The levels of B3GNT3 protein were determined using the HPA database and western blot, indicating higher expression in LUAD tissues and LUAD cells than in normal lung tissues and human bronchial epithelial cells, respectively. Consistent with our findings, B3GNT3 was revealed as a carcinogenic factor by presenting higher expression in pancreatic cancer (16), early-stage cervical cancer (15), neuroblastoma (14), and endometrial cancer tissues than in normal tissues (29). In our study, high levels of B3GNT3 were associated with poor prognosis with advanced stage and higher mortality rates, which was also indicated in previous lung cancer (19) and non-small cell lung cancer studies (12).…”
Section: Discussionsupporting
confidence: 92%
“…B3GNT3, Beta-1,3-N-acetylglucosaminyltransferase 3, is a type II transmembrane protein located in the Golgi apparatus and is essential for forming extended core 1 oligosaccharides (10,11). Numerous studies have reported the involvement of B3GNT3 in malignant transformation and B3GNT3 expression is strongly correlated with PD-L1 levels and EGFR mutation status (12)(13)(14)(15)(16)(17)(18)(19). It has been indicated that B3GNT3 expression is strongly correlated with PD-L1 levels and EGFR mutation status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B3GNT3 is a type II transmembrane protein located in the Golgi apparatus. It is involved in the biosynthesis of the polyacetamide chain, generation of principal components of dimeric sialic acid Lewis A, regulation of l-selectin ligand function, lymphocyte trafficking and attribution of T cells (19)(20)(21)(22). The B3GNT3 gene is located on chromosome 19q13.1 and belongs to the β3GlcNAcT gene family, which contains at least 8 different β3GlcNAcT genes.…”
Section: Discussionmentioning
confidence: 99%
“…It mainly plays tumor-promoting activity in various types of tumors, including pancreatic [58,59], cervical [60], endometrial [61], and lung cancer [62,63]. In some instances, the expression of B3GNT3 inhibits the anti-cancer immune response, as in pancreatic [64], breast [65] and lung cancer [66]. In particular, in triple negative breast cancer, B3GNT3 promotes through EGFR the interaction between PD-1 and PD-L1, resulting in This reaction is mediated by different B3GNTs, specific to several types of sugar chains (e.g., type 2 chains for B3GNT4 and B3GNT7, glycolipids for B3GNT5, O-linked for B3GNT9).…”
Section: Polylactosaminic Chainsmentioning
confidence: 99%